Hyposmia: an underestimated and frequent adverse effect of chemotherapy - Riga, Maria; Chelis, Leonidas; Papazi, Theano; Danielides, Vasilios; Katotomichelakis, Michael; Kakolyris, Stylianos (Supportive care in cancer, 2015)
Objectives Optimal function of both the olfactory sensory neurons and the olfactory mucosa is a prerequisite for normal olfactory perception. Both the olfactory neurons and mucosa might be subjects to the neurotoxic and mucotoxic effects of chemotherapy. Despite the recognized importance of olfaction in nutrition and quality of life, the potential olfactory toxicity of chemotherapy regimens has not been adequately assessed. The aim of this study is to investigate whether mucotoxic and/or neurotoxic drugs compromise olfactory performance. Patients and methods Forty-four consecutive patients completed the “Sniffin’ Sticks” test, an objective quantitative/qualitative method to assess olfactory function, at diagnosis and immediately before the infusion of the last session of three to four chemotherapy cycles, according to the therapeutic protocol. The patients underwent therapy containing oxaliplatin and antimetabolites (5-FU or capecitabine; O+A group), taxanes and platinum analogues (cisplatin and carboplatin; T+P group), or taxanes and anthracyclines (doxorubicin or liposomal doxorubicin; T+A group). Results A significant decrease was noted for olfactory threshold (OT), olfactory discrimination (OD), olfactory identification (OI), and the composite threshold–discrimination–identification (TDI) score. A significant deterioration of all olfactory indices was found for each chemotherapy group. Pairwise comparisons revealed significant differences between the O+A and the T+P group regarding OT and TDI. TDI scores were significantly lower after chemotherapy in all age groups. Patients older than 50 years were found to be more susceptible to olfactory toxicity than younger patients. Conclusions Patients who undergo chemotherapy experience significant compromise in their olfactory function. A grading system for olfactory toxicity is proposed.